GERM-18. RELAPSE PATTERN AND TREATMENT OUTCOME OF RECURRENT CENTRAL NERVOUS SYSTEM GERM CELL TUMORS. Issue 2 (22nd June 2018) - Yanagisawa, Takaaki; Suzuki, Tomonari; Fukuoka, Kohei; Adachi, Junichi; Mishima, Kazuhiko; Nishikawa, Ryo; Fujimaki, Takamitsu; Matsutani, Masao; Yamaoka, Masayoshi; Ohyama, Wataru; Yokoi, Kentaro; Akiyama, Masaharu; et al.
Abstract: BACKGROUND: Central nervous system germ cell tumors (CNS-GCT) are a heterogeneous group of diseases. The management of CNS-GCT remains controversial. Objective: To clarify the relapse pattern and outcome of patients with recurrent CNS-GCT in order to find problems with current initial management. METHODS: Chart review of patients with recurrent CNS-GCTs treated in two institutions from 2007 to 2017. RESULTS: There were 19 germinomas and six non-germinomatous germ cell tumors (NGGCT), referred to us for the first (n=19), second (n=4), third (n=1) and fourth (n=1) relapse. The time from the diagnosis to the first relapse was within three years for 15 patients (range 6- 24 months) and over three years (range 36 -144 months) for 10 patients. The site of recurrence was outside the irradiation field for 13 germinoma cases, and inside for six germinoma and six NGGCT patients. Thirteen patients with first recurrent germinoma survived with chemotherapy and re-irradiation, and one failed with high-dose chemotherapy only. Two patients with second relapse of germinoma were successfully treated with high-dose chemotherapy only. One patient with second relapse of germinoma refractory to chemotherapy and re-irradiation is alive with oral metronomic etoposide for nine years. Only one of six NGGCT patients survived in spite of intensive treatments. CONCLUSIONS: Germinoma patients treated with reduced radiotherapy and chemotherapy can relapse both within and outside irradiation fields, very early and very late in longer follow-up. These results can teach us not only the optimal management of recurrent disease, but also suggest possible novel management of initial disease.